Justin Trudeau's Intended Resignation: Implications for Immigration Reforms, United States - Canada Trade Relations, And Geostrategic Politics in North America During Donald Trump’s Resumption in The Oval Office - Ugo Chuks Okolie; Anthony C. Nwokolobia (ARISTO, 2026)
This study explored the potential effects of Justin Trudeau's planned resignation on immigration reforms, U.S.-Canada trade relations, and geostrategic dynamics in North America under Donald Trump's presidency. Using a historical research approach, the study examined the political developments and policy changes during Trudeau's time in office, considering their future implications following his expected departure. The study utilized the Realist Theory of International Relations, focusing on the role of national interest and power in shaping relationships between states. The findings suggest that Trudeau’s resignation could lead to significant shifts in Canada’s immigration policies, potentially resulting in more restrictive measures aligned with conservative ideologies. In terms of trade, U.S.-Canada relations, already complicated by Trump’s protectionist stance and the USMCA renegotiation, may face greater instability, impacting the region’s economic stability. Furthermore, Trudeau’s departure could alter the geostrategic balance in North America, diminishing Canada’s diplomatic influence in trilateral negotiations with the U.S. and Mexico, as well as its position in global affairs. The study concluded that Trudeau's resignation would create a leadership gap that could challenge Canada’s policy continuity and international relationships. The study recommended among others that Canada should diversify its trade relationships to lessen dependence on the U.S., focusing on building stronger connections with emerging economies in Asia, the EU, and Africa.